Evaluasi Efektivitas Sistem Pengendalian Internal Proyek Pemerintah di Bawah Pengawasan PT. Pembangunan Perumahan (Persero) Tbk. - Karoyani, Made Win; Dwirandra, A.A. Ngurah Bagus (E-Jurnal Akuntansi, 2019)
The sample in this study was released by 35 people with Non-Probability methods, especially Purposive Sampling (Sample Considerations). The method of data collection is done through questionnaires, observations, and interviews. The analysis technique used is the analysis of comparative quantitative descriptive data. Based on the results of the analysis, the internal control system and the SPI dimension are all included in the effective category, but for each dimension, the SPI of various assessment results is effective and very effective. Based on the results of the respondents' scores, all of these scores have not reached a maximum value of 6, so that both the internal control system, internal control system dimensions, or from each dimension still need to be improved. Keywords: SPI, dimensions, elements, effectiveness